Case report of primary intestinal lymphangiectasia diagnosed in an octogenarian by ileal intubation and by push enteroscopy after missed diagnosis by standard colonoscopy and EGD. Issue 3 (January 2018) - Cappell, Mitchell S.; Edhi, Ahmed; Amin, Mitual
Abstract: Rationale: Primary intestinal lymphangiectasia (PIL) is a rare, presumably congenital lesion that is usually diagnosed in patients < 3 years old, is rarely first diagnosed in adulthood, and when first diagnosed in adulthood typically presents with symptoms for many years. Although PIL is often identified by endoscopic abnormalities, it must be emphasized that the jejunoileum/distal duodenum must be intubated for diagnosis because the lesions are present in these regions. This work demonstrates that 1)-PIL can occur in an octogenarian; 2)-shows that the characteristic endoscopic findings are not found at colonoscopy without terminal ileal intubation; and 3)-may be missed at standard EGD without distal duodenal intubation. Diagnoses: A patient initially presented at age 83 with symptoms of watery diarrhea, abdominal distention, 5-Kg-weight-gain, and weakness for one month, and had typical clinical findings of PIL including chylous ascites, pleural effusions, bilateral pitting leg edema, hypoalbuminemia, borderline lymphopenia, hypovitaminosis-D, and hypocalcemia. Protein-losing-enteropathy was demonstrated by positive stool tests for alpha-1-antitrypsin. Standard colonoscopy revealed no significant lesions, but terminal ileal intubation during colonoscopy demonstrated creamy-white, punctate, mucosal lesions in terminal ileum, characteristic of lymphangiectasia. EGD with intubation to mid-descending duodenum revealed no significant lesions, but subsequent enteroscopy demonstrated lesions in distal duodenum/proximal jejunum similar to those in terminal ileum characteristic of lymphangiectasia. Histopathologic analysis of lesions of terminal ileum/distal duodenum demonstrated dilated mucosal vessels, confirmed as lymphatic vessels by immunohistochemistry. PIL was diagnosed after excluding secondary causes of intestinal lymphangiectasia. Interventions/Outcomes: Patient placed on standard PIL diet: oral supplements of medium-chain triglycerides, a high protein diet, supplements of fat-soluble vitamins, and avoiding long-chain fatty acids, with marked clinical improvement. Lessons: This work shows that: 1)-standard EGD and colonoscopy may miss characteristic lesions of PIL, 2)-enteroscopy or terminal ileal intubation at colonoscopy may be required for the diagnosis because lesions are typically located in distal duodenum/jejunoileum; and 3)-PIL can first present in the very elderly even with symptoms of short duration.